Representaciones sociales de un grupo de mujeres, sobre las expresiones alusivas al género femenino en letras de canciones de reggaetón. (2023)
The objective of this study was to analyze the social representations that a group of women have about the expressions alluding to the female gender present in the lyrics of reggaetón songs. Taking into account the literature review, it became evident that there are previous researches that have studied this topic, but they differ in the chosen population, since most of them emphasize young people, and the interest of this study is women between 18 and 30 years old belonging to the city of Santiago de Cali.